Chinese Expert Consensus on Full-Cycle Rehabilitation of Coronary Heart Disease in the Elderly - DONG Anqin; JIA Jie; CHEN Xin; DING Yipeng; YE Xujun; HE Jing; ZHENG Pengyuan; LIAO Weijing; ZHENG Jiejiao; CHEN Zuobing; YAO Liqing; ZHOU Xue; et al. (康复学报)
Coronary atherosclerotic heart disease (CHD) is one of the main causes affecting the health of elderly people (≥65 years old). CHD is a threat to the life and health of the elderly, and also brings huge economic burden to families and society. Because the elderly often have the underlying diseases such as hypertension, diabetes, hyperlipemia, etc., which seriously affect the occurrence and progress of CHD, the prevention and treatment task of CHD in the elderly is facing a huge challenge. How to reduce the recurrence rate of cardiovascular events, prolong life span and improve the quality of life of the elderly through standardized and individualized full-cycle rehabilitation management has been a research hot spot. With the support of the relevant departments of the National Health Commission, led by the team of the national key research and development program "Research on the Technology System and Information Management of the Elderly Full Cycle Rehabilitation (2018YFC2002300)", the project organized a multidisciplinary panel of domestic experts to write the expert consensus on Full-Cycle Rehabilitation of Coronary Heart Disease in the Elderly. The aim of this consensus is to provide a comprehensive health care system based on bio-psycho-social medical model for the elderly with CHD. This expert consensus elaborated the full-cycle rehabilitation assessment and treatment of CHD in the elderly, providing a scientific guidance for the safety and effectiveness of CHD rehabilitation in the elderly, and promoting the development of elderly CHD full-cycle rehabilitation in China.